EVOLUSI KEBIJAKAN PUBLIK DI INDONESIA: KAJIAN INKREMENTAL DALAM REFORMASI PENDIDIKAN DAN OTONOMI DAERAH - zaskia Afrina Khaliq; Hafidatus Solehah Solehah; Naufal Hafizh W; Nevila Marta Mevia; Ria Angin (Empat Sembilan Publisher, 2025)
The transformation of public policy in Indonesia takes place gradually and accumulatively, not through radical changes. The analytical framework of policy evolution theory can be used to understand this change as an adaptive process to internal and external dynamics. This research aims to describe the application of the incremental approach in education reform and regional autonomy in Indonesia. Utilizing a desk study method, the article traces patterns of policy change through analysis of academic literature. The findings reveal that curriculum reform and decentralization policy revision clearly embody evolutionary principles, such as institutional selection, collective learning, and adaptation to environmental pressures. The conclusion of the article emphasizes the relevance of the policy evolution approach to understand the complexity and contextuality of governance change in Indonesia.